Eksistensi Budaya Tea Bel (Pela Gandung) Dalam Kehidupan Suku Kei Di Kabupaten Maluku Tenggara - Kayus Jamlean (Jurnal Rumpun Ilmu Kesehatan, 2023)
Culture is a national identity that must be respected and maintained and needs to be preserved so that culture is not lost and becomes a legacy for our children and grandchildren. Of course, this is the responsibility of the younger generation to preserve this culture. This is because culture is one of the identities of a country. As human civilization progresses today, the threat of globalization to the existence of the country's identity can be assessed from the increasing erosion of traditional culture among society, especially the younger generation.